Trends in nanotechnology-based delivery systems for dermal targeting of drugs: an enticing approach to offset psoriasis. (2nd June 2020) - Saleem, Sadaf; Iqubal, Mohammad Kashif; Garg, Sanjay; Ali, Javed; Baboota, Sanjula
ABSTRACT: Introduction: Psoriasis is identified as an inflammatory, chronic, auto-immune disease requiring long-term treatment, imposing an unnecessary burden on the patient. A significant impediment for the treatment of dermatological disorders via transdermal route is the inability of drug molecules to cross the stratum corneum (SC), as the larger size of drug molecules inhibits them to pervade into the skin, thus hampering their absorption. Some drugs exhibit systemic side-effects, which curbs patient compliance, resulting in treatment discontinuation. Areas covered: This review aims to describe the detailed study such as demographic status, molecular factors of psoriasis, treatment with emerging combination therapy and role of nanotechnology tools in the treatment of psoriasis. Expert opinion: To overcome problems related to the conventional drug delivery system, several nanotechnology-based formulations have been devised to enhance bioavailability, drug permeation and accumulation in the skin. Nano-formulations provide better permeation, targeted delivery and enhanced efficacy, thus gaining enormous popularity for cutaneous disorders. This pervasive review provides an overview of the pathophysiology of the disease, its molecular targets and the available herbal, synthetic and combination treatment modalities. The review also systematizes recent works utilizing nano-carriers to improve the treatment denouement of psoriasis.